Pemanfaatan Teknik Konseling Behavior dalam Meningkatkan Kepercayaan Diri Terhadap Santri: Utilization of Behavioral Counseling Techniques in Increasing Self-Confidence in Students - Bahrul Ulum Zuhri; Sriharini (Sociocouns: Journal of Islamic Guidance and Counseling, 2023)
Humans, including students at the Tamrinut Tullab Islamic boarding school, require self confidence to perform daily tasks. this relatively new Islamic boarding school, Tamrinut Tullab, in Ngaglik, Sleman Daerah Istimewa Yogyakarta, has not categorized students to learn to participate in activities, and some students have never  had experience in the cottage so they experienced cultural shock that has an impact on their confidence. The main issue being researched in this journal is how to use behavior counseling techniques to help students at the Tamrinut tullab Islamic boarding school in Ngaglik, Sleman, Daerah Istimewa Yogyakarta feel more confident about themselves. This journal aims to describe how behavior counseling techniques are used to help students feel more confident. The findings of this study demonstrate how behavior counseling techniques can be used to help students feel more confident, develop an adaptable attitude, participate fully in activities at their Islamic boarding school, and make many other positive changes.